2002
DOI: 10.1046/j.1365-2222.2002.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of interleukin‐5 secretion from drug‐specific activated ex vivo peripheral blood mononuclear cells as a test system for the in vitro detection of drug sensitization

Abstract: These data suggest a role for the determination of drug-specific IL-5 secretion by ex vivo peripheral blood mononuclear cells for the in vitro detection of drug-sensitization in drug-induced maculopapular exanthems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
4
61
2
5
Order By: Relevance
“…9,42,43 Another test used in research concerns the assessment of serum IL-5 levels secreted by peripheral blood mononuclear cells in the presence of the analyzed drug. 44 This test has a diagnostic sensitivity of 92%, which is higher than that of the lymphocyte transformation test (78%) or of the patch tests (55%). This test is not performed as a routine practice.…”
Section: Clinical Picture and Diagnosismentioning
confidence: 93%
“…9,42,43 Another test used in research concerns the assessment of serum IL-5 levels secreted by peripheral blood mononuclear cells in the presence of the analyzed drug. 44 This test has a diagnostic sensitivity of 92%, which is higher than that of the lymphocyte transformation test (78%) or of the patch tests (55%). This test is not performed as a routine practice.…”
Section: Clinical Picture and Diagnosismentioning
confidence: 93%
“…For CD69 upregulation, HSA can be used instead of AB serum and cells need to be cultured for only 2-3 days [76]. Alternatively, as used in several studies, cytokines can be measured in the cell culture supernatant: the determination of IL-5 in PBMCs from ten patients with exanthema from amoxicillin showed a sensitivity of 92% and a specificity of 100% [77]. In another study, IFN-c was measured in 36 patients with cutaneous drug reactions [78] and showed a sensitivity of 78%.…”
Section: Topic 2: Drug-reactive T Cellsmentioning
confidence: 99%
“…B. Typ-1-Sofort-Reaktion vs. Typ-IV-delayed-typehypersensitivity-Reaktion), jetzt auch durch die Aktivierung verschiedener TZell-Subpopulationen (TH2 bzw. TH1) und die Produktion ihrer spezifischen Zytokinmuster pathophysiologisch erklärt werden [4,5]. Die Untersuchung, ob bestimmte Umweltstoffe eher Makrophagen-/Monozyten-Zytokine, TH1-oder TH2-Zytokine induzieren, könnte daher künftig helfen, mögliche Reaktionsmuster gegenüber solchen Substanzen vorherzusagen bzw.…”
Section: Aufklärung Von Pathomechanismenunclassified
“…Eine umfangreiche wissenschaftliche Literatur weist auf die Beteiligung von Zytokinen auch bei Umweltexpositionen und -krankheiten hin.Wegen der aktuellen Bedeutung der Zytokine und der zunehmenden Verfügbar-keit von Untersuchungskits erscheint es zunächst logisch, dass Zytokinbestimmungen im Rahmen der Diagnostik von Umwelterkrankungen vorgenommen und propagiert werden [1, 2,3], zumal sie im Rahmen der Allergiediagnostik bereits einen gewissen Stellenwert haben [4,5,6,7,8]. Jedoch sind die Zytokinmuster sehr variabel und reagieren auf viele Einflüsse, sodass einzelnen Bestimmungen im Blut in der Regel kein diagnostischer Aussagewert zukommt.…”
Section: Introductionunclassified